La démarche d'enquête de Dewey : un levier pédagogique au service de la formation des adultes éloignés de l'emploi - Thierry Piot (Université de Provence, 2017)
This paper focuses on the investigation process of Dewey, which is characterized by the fact that this author is a pragmatist. From a pedagogical point of view, the process is affiliated within a training system aimed at adults who are far from employment. The results show that the current thinking on the writings of Dewey is in two separate directions: (1) the interest to mobilize a « pedagogy of inquiry » to place the adults in training in a logic of reflexivity and development of their empowerment; (2) the centrality of language interactions adjusted to constitute mediation between action and reflection and to allow a mobilization of individuals in their training course.